2011
DOI: 10.1111/j.1447-0349.2010.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Model for investigating the benefits of clinical supervision in psychiatric nursing: A survey study

Abstract: The objective of this study was to test a model for analysing the possible benefits of clinical supervision. The model suggested a pathway from participation to effectiveness to benefits of clinical supervision, and included possible influences of individual and workplace factors. The study sample was 136 nursing staff members in permanent employment on nine general psychiatric wards and at four community mental health centres at a Danish psychiatric university hospital. Data were collected by means of a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 27 publications
(52 reference statements)
3
59
2
2
Order By: Relevance
“…Overall, the result of the CFA supported the theoretical construction modelled on previous empirical studies (Edwards et al. 2006a, Gonge & Buus 2011). The most important factors were Trust/Rapport and Supervisor advice/Support, Improved care/Skills and Reflection.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, the result of the CFA supported the theoretical construction modelled on previous empirical studies (Edwards et al. 2006a, Gonge & Buus 2011). The most important factors were Trust/Rapport and Supervisor advice/Support, Improved care/Skills and Reflection.…”
Section: Resultssupporting
confidence: 81%
“…The MCSS employed in the present study has been translated into Finnish by Hyrkäs et al. (2003) and into Danish by Gonge and Buus (2010, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational stress in nursing is of global concern (Lambert & Lambert , Wong et al . , Gonge & Buus , Hamdan‐Mansour et al . , Ward , Happell et al .…”
Section: Introductionmentioning
confidence: 99%
“…A noticeable exception was Buus and Gonge's () sequential mixed‐methods study of participation and outcomes of group clinical supervision, which combined organizational register data, survey data, observational data, and interview data. An examination of the survey sample ( n = 145) indicated that the sample was not representative of the population ( n = 239), and that participation in the survey was significantly linked to participation in supervision (Gonge & Buus , ). The interview study sample ( n = 22) was drawn from the survey sample, and there were no statistical differences between these samples (Buus et al .…”
Section: Introductionmentioning
confidence: 99%